Pengaruh Kualitas Pelayanan Dan Store Atmosphere Terhadap Loyalitas Konsumen Pada Kafe Lantai Dua Coffee dan Resto Siak Sri Indrapura - Nidya Astantika; Lie Othman; Syofiatul Safitri (eCo-Buss, 2023)
This study aims to determine the effect of service quality and store atmosphere on customer loyalty partially and simultaneously. This study used a quantitative descriptive analysis method, with the data source of this research coming from primary data obtained through the process of distributing questionnaires which were then tested using the SPSS application. The population in this study were all consumers who had visited at least twice at the Kafe Lantai Dua Coffee and Resto in Siak Sri Indrapura Resto and the sample taken was 100 respondents using the slovin formula. Determination of the sample in this study using the slovin formula, namely the Purposive Sampling technique with the type of Non Probabality technique. Data analysis used validity test, reliability test, classical assumption test, simple and multiple linear regression analysis test. In this study the results obtained were that Service Quality (X1) had a positive and significant effect on Consumer Loyalty (Y), and Store Atmosphere (X2) had a positive and significant effect on Consumer Loyalty (Y) and Service Quality (X1) and Store Atmosphere (X2). ) has a positive and significant effect on Consumer Loyalty (Y) at the Second Floor Coffee Cafe and Siak Sri Indrapura Resto.